Idiopathic distal sensory polyneuropathy: ACTTION diagnostic criteria. (1st December 2020) - Freeman, Roy; Gewandter, Jennifer S.; Faber, Catharina G.; Gibbons, Christopher; Haroutounian, Simon; Lauria, Giuseppe; Levine, Todd; Malik, Rayaz A.; Singleton, J. Robinson; Smith, A. Gordon; Bell, Josh; Dworkin, Robert H.; et al.
Abstract : Objective: To present standardized diagnostic criteria for idiopathic distal sensory polyneuropathy (iDSP) and its subtypes: idiopathic mixed fiber sensory neuropathy (iMFN), idiopathic small fiber sensory neuropathy (iSFN), and idiopathic large fiber sensory neuropathy (iLFN) for use in research. Methods: The Analgesic, Anesthetic, and Addiction Clinical Trial Translations, Innovations, Opportunities and Networks (ACTTION) public-private partnership with the Food and Drug Administration convened a meeting to develop consensus diagnostic criteria for iMFN, iSFN, and iLFN. After background presentations, a collaborative, iterative approach was used to develop expert consensus for new criteria. Results: An iDSP diagnosis requires at least 1 small fiber (SF) or large fiber (LF) symptom, at least 1 SF or LF sign, abnormalities in sensory nerve conduction studies (NCS) or distal intraepidermal nerve fiber density (IENFD), and exclusion of known etiologies. An iMFN diagnosis requires that at least 1 of the above clinical features is SF and 1 clinical feature is LF with abnormalities in sensory NCS or IENFD. Diagnostic criteria for iSFN require at least 1 SF symptom and at least 1 SF sign with abnormal IENFD, normal sensory NCS, and the absence of LF symptoms and signs. Diagnostic criteria for iLFN require at least 1 LF symptom and at least 1 LF sign with normal IENFD, abnormal sensory NCS, and absence of SF symptoms and signs. Conclusion: Adoption of these standardized diagnostic criteria will advance research and clinical trials and spur development of novel therapies for iDSPs.